IMPLEMENTASI KEBIJAKAN PENANGANAN PENGAMEN JALANAN DI KOTA SERANG - Iip Mualip, Angga Rosidin (LP2M Universitas Muslim Nusantara Al Washliyah, 2022)
This study aims to: Knowing how the implementation of the Mayor of Serang Regulation Number 41 of 2017 concerning the Implementation of Regional Regulation Number 2 of 2010 concerning the Prevention, Eradication and Management of Community Diseases (Policy for Handling Street Singers in Serang City)